Independent Effects of Body Fat and Inflammatory Markers on Ventricular Geometry, Midwall Function, and Atrial Remodeling. Issue 3 (7th January 2014) - Lai, Yau‐Huei; Liu, Chuan‐Chuan; Kuo, Jen‐Yuan; Hung, Ta‐Chuan; Wu, Yih‐Jer; Yeh, Hung‐I; Bulwer, Bernard E.; Hung, Chung‐Lieh
Abstract Background The effect of body fat distribution on left ventricular (LV) mass and geometry has been recently recognized. However, data regarding circulating inflammatory markers in relation to regional visceral fat deposits, which are metabolically active tissues that can impact cardiac structural remodeling, remain sparse. Hypothesis We hypothesized that obesity has adverse effects on cardiac function and structure. Methods We consecutively studied 1071 asymptomatic subjects (age 49.5 ± 10.5 years, 39.4% female) free from significant valvular disorders, chronic lung disease, or renal disease. Echocardiography‐defined cardiac structures and LV geometries including LV mass, mass‐to‐volume ratio, and fractional shortening were all determined. Body fat composition (Tanita‐305 Body‐Fat Analyzer; Tanita Corp., Tokyo, Japan) was obtained and calculated. Multivariate regression models from various models were used to represent the independent association between body fat and echo‐derived ventricular mass and geometries. Results In multivariable analysis, increasing body fat was significantly related to increase in left atrial (LA) and LV diameter, posterior wall thickness, relative wall thickness (RWT), LV mass, mass‐to‐volume ratio, and decreased midwall fractional shortening with or without stress correction (all P < 0.001). When LV mass and severity of mitral regurgitation was further added, the independent association between increased body fat composition and larger LA diameter remained significant (β coefficient = 0.37, P < 0.001). Elevated high‐sensitivity C‐reactive protein (Hs‐CRP) level was associated with larger LA diameter, increased RWT, and worsened midwall mechanics in the female gender (all interaction P < 0.05). Conclusions Accumulated body fat seemed to be related to worse ventricular midwall contractility and atrial remodeling, particularly in the female gender, with high systemic inflammation. These gender and Hs‐CRP–specific modification effects may potentiate the pathological mechanisms involved in heart failure with preserved ejection fraction.